1998
DOI: 10.1177/000348949810700302
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Gas Exchange in the Middle Ear of Guinea Pigs

Abstract: Gas exchange between blood in the middle ear (ME) mucosa and ambient ME gas may be limited by diffusion through tissue or blood perfusion. In order to study the limiting factors in ME gas exchange, a hole was drilled in the bulla of 14 anesthetized guinea pigs through which a mass spectrometer probe was inserted and sealed in place. The rate at which oxygen (O2), carbon dioxide (CO2), nitrogen, and argon concentrations changed toward their steady state values was recorded. From the exponential fitted curves, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 15 publications
4
20
0
Order By: Relevance
“…Because the calculation of time constants assumes a closed ME, the model equation attributes the decrease in gas partial pressure caused by venting to transmucosal transfers, thereby artificially inflating the estimated value of the time constants of gases in decreasing magnitude from the most representative to the least representative species. Consequently, experiments that fail to control for this effect will generate downwardly biased estimates of the C02:N2 and C02:02 timeconstant ratios (as was reported by Mover-Lev et al, 19 in comparison to the values reported for monkey experiments) and of the N2:02 time constant ratios (not reported, but consistent with the data presented in the Figure).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Because the calculation of time constants assumes a closed ME, the model equation attributes the decrease in gas partial pressure caused by venting to transmucosal transfers, thereby artificially inflating the estimated value of the time constants of gases in decreasing magnitude from the most representative to the least representative species. Consequently, experiments that fail to control for this effect will generate downwardly biased estimates of the C02:N2 and C02:02 timeconstant ratios (as was reported by Mover-Lev et al, 19 in comparison to the values reported for monkey experiments) and of the N2:02 time constant ratios (not reported, but consistent with the data presented in the Figure).…”
Section: Resultssupporting
confidence: 84%
“…The results of the model simulations document 3 major sources of error in the estimates of the time constants for transmucosal gas exchange presented by Mover-Lev et al 19 The first is a systematic error introduced by the design of the experiment. There, the assumption of a closed ME volume is not consistent with the predicted venting, via the eustachian tube, of gas at total ME pressures in excess of the tubal opening pressure.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations